Some contributions on analysis of chaotic dynamical systems - Ummu Atiqah Mohd Roslan (Fakulti Sains dan Teknologi, 2012)
Chaos is a property of dynamical system which is completely unordered, unpredictable, uncontrolled and has a sensitive dependence on initial condition as the main features of chaos.